2018
DOI: 10.1111/cen.13881
|View full text |Cite
|
Sign up to set email alerts
|

Role of fibroblast growth factor 21 in gestational diabetes mellitus: A mini‐review

Abstract: Gestational diabetes mellitus (GDM) is defined as glucose intolerance with onset or first diagnosis during pregnancy, but not to the level of being diagnostic for diabetes in a nonpregnant adult. 1 During pregnancy, maternal tissues become progressively insensitive to insulin due to metabolic changes that ensure adequate nutrition is supplied to the foetus. 2,3 One such change is that insulin-mediated whole-body glucose disposal decreases by 40%-60%, necessitating a 200%-250% increase in insulin secretion in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…Chen et al found that FGF21 levels increased progressively with dysglycemia and concluded that FGF21 could predict the development of diabetes in a large Chinese prospective study [25]. To our knowledge, ours is the first meta-analysis of the relationship between circulating FGF21 levels and GDM although previously, systematic reviews have bene published by Yuan et al and Bellos et al [9,26]. In both reviews of Yuan et al and Bellos et al, statistical analysis was not performed to draw an exact conclusion between circulating FGF21 levels and GDM.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Chen et al found that FGF21 levels increased progressively with dysglycemia and concluded that FGF21 could predict the development of diabetes in a large Chinese prospective study [25]. To our knowledge, ours is the first meta-analysis of the relationship between circulating FGF21 levels and GDM although previously, systematic reviews have bene published by Yuan et al and Bellos et al [9,26]. In both reviews of Yuan et al and Bellos et al, statistical analysis was not performed to draw an exact conclusion between circulating FGF21 levels and GDM.…”
Section: Discussionmentioning
confidence: 76%
“…Some reported a difference in circulating FGF21 levels between pregnant women with GDM and those without, while other studies failed to identify a significant difference in FGF21 levels between GDM patients and pregnant women with normal glucose tolerance (NGT). Yuan et al performed a mini-review to evaluate the role of FGF21 in GDM, but they were unable to provide further clarification [9]. To investigate the relationship between FGF21 levels and GDM, we performed a meta-analysis.…”
mentioning
confidence: 99%
“…Other inflammatory markers upregulated in pediatric AD included proteins involved in tissue remodeling (matrix metalloproteinase [MMP3], MMP9, MMP10, myeloblastin), T-cell activation (IL2RA or CD25, a receptor component of the T-cell growth factor IL-2), lipid metabolism (fatty acid binding protein-4 [FABP4], a treatment target in cardiovascular disease and diabetes 52 ), and angiogenesis/coagulation (urokinase receptor). We also found increases in growth factors FGF21 (fibroblast growth factor-21), a liverderived molecule that is increased in insulin-resistant morbidities such as type 2 diabetes mellitus or obesity, 53 and transforming growth factor (TGF)-a, an analogue of epidermal growth factor mediating epithelial development, epidermal hyperproliferation, and tumorigenesis. Other upregulated molecules included the potent leukocyte chemoattractants CCL2 and CCL15, neutrophil protein myeloperoxidase (MPO), lymphotoxin-b receptor LTBR (a member of the tumor necrosis factor receptor superfamily involved in lymphoid tissue development), and the IL-1 decoy receptor IL1R2, which limits IL-1-a/b pathway activation by preventing receptor binding of IL-1a and IL-1b.…”
Section: Proteomic Differences In Peripheral Blood Between Early Pediatric and Adult Admentioning
confidence: 80%
“…An increase in circulating blood methionine (Met) and altered Met catabolism led to excessive conversion of Met into S-adenosylmethionine by a liver-specific Met adenosyltransferase, and thus to diabetes pathogenesis (insulin-resistant and β-cell dysfunctions) 9,26,27 . By controlling Met levels, the conditions of glucose homeostasis, insulin sensitivity, and oxidative stress with activation of the fibroblast growth factor 21 and protein phosphatase 2A signals in diabetes may improve 28,29 . As previously reported, increased or reduced concentrations of PC aa C36:1 or SM(OH) C22:2 in plasma indicated the incidence of T2D 12,20 .…”
Section: Discussionmentioning
confidence: 99%